2020
DOI: 10.1111/papr.12963
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pain Neuroscience Education Followed by Motor Control Exercises With Group‐Based Exercises for Chronic Low Back Pain: A Randomized Controlled Trial

Abstract: Background: Different individualized interventions have been used to improve chronic low back pain (CLBP). However, their superiority over group-based interventions has yet to be elucidated. We compared an individualized treatment involving pain neuroscience education (PNE) plus motor control exercise (MCE) with group-based exercise (GE) in patients with CLBP. Methods: Seventy-three patients with CLBP were randomly assigned into the PNE plus MCE group (n = 37) and GE group (n = 36). Both PNE plus MCE and GE we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 28 publications
6
33
1
Order By: Relevance
“…Of these studies, 12 (60%) clearly reported that no adverse events occurred in any intervention group. 55 67 76 82 85 89 90 95 96 97 98 99 One study comparing cognitive behavioural therapy with no intervention reported that no serious adverse effects (defined as death or admission to hospital, events attributable to the intervention, or events that caused unwarranted distress to a participant) occurred in either group, during the intervention period. 47 Four studies reported on the occurrence of adverse events during the intervention period 54 61 100 101 ; however, none was related to the psychological interventions under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 12 (60%) clearly reported that no adverse events occurred in any intervention group. 55 67 76 82 85 89 90 95 96 97 98 99 One study comparing cognitive behavioural therapy with no intervention reported that no serious adverse effects (defined as death or admission to hospital, events attributable to the intervention, or events that caused unwarranted distress to a participant) occurred in either group, during the intervention period. 47 Four studies reported on the occurrence of adverse events during the intervention period 54 61 100 101 ; however, none was related to the psychological interventions under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the comparison of the two exercise programs showed a greater effect of motor control with cognitive purpose compared to the core stability exercises on the variables of pain and disability (VAS and RMDQ, respectively). A possible justification could be associated with the individualized, PNE treatment employed using cognitive-based education followed by an exercise program as previously suggested [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more knowledge of spinal motor dysfunction in patients with CLBP has emerged [ 16 , 17 ]. Patients with CLBP that present reduced motor control usually have difficulties to control postures and movements [ 16 , 18 ].Therefore, addressing pain recognition and a better spinal muscle function to improve spinal motor control could be more effective [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results from the PEDro scale data, almost all studies were judged to be at low risk of bias for most of the items. Two studies were considered at high evidence level (level I) [ 21 , 23 ], nine studies at evidence level II [ 11 , 12 , 13 , 15 , 16 , 17 , 19 , 20 , 22 ] and two (one of which has a quasi-experimental design) with a low level of evidence [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the 13 studies were discussed separately, depending on the outcome measures investigated. According to pain reduction, investigated through VAS, NRS, NRS-11, PBI and CPAQ, six studies [ 11 , 12 , 14 , 18 , 19 , 23 ] out of thirteen significantly supported more evidence in the experimental group than in the control group. Moreover, in favor of the experimental group and to the detriment of the control group, another study [ 23 ] showed modest improvements, and one [ 17 ] showed a moderate reduction in painful symptoms detected after surgery, but which was not maintained at subsequent endpoints of follow-up.…”
Section: Discussionmentioning
confidence: 99%